Cover Picture: Size‐Dependent Surface Migration of Au Alloys on Si Nanowires at Different Cooling Rates (Chem. Asian J. 24/2016). Issue 24 (12th December 2016) - Park, Yi‐Seul; Kim, Hyun Ji; Lee, Jin Seok
Abstract : The surface migration behavior of Au alloys was investigated through the variation of cooling conditions after growth of vertically aligned Si nanowires (SiNWs) by an Au catalyst‐assisted vapor–liquid–solid mechanism. The Au alloy showed a size‐dependent surface migration behavior at the top of the SiNWs with varying cooling rate. During fast cooling, the Au alloy stayed at the top of the SiNWs regardless of the Au alloy diameter. In contrast, during slow cooling, the small Au alloys migrated from the top to the sidewalls of the SiNWs, whereas the large Au alloys did not migrate from the top of the SiNWs caused by Au–Si eutectic stability. More information can be found in the Communication by Jin Seok Lee et al. onpage 3487 in Issue 24, 2016 (DOI:10.1002/asia.201601325 ).